HISTOPATHOLOGICAL CHANGES OF USING RAW LENTIL SEEDS AS A PARTIAL SUBSTITUTE FOR THE FISH MEAL IN DIETS OF THE COMMON CARP CYPRINUS CARPIO L. - Nasreen M. Abdulrahman,; Z. S. Abdulla,; S. M. Hassan, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was carried out at College of Veterinary Medicine, University of Sulaimani. Microscopically, no adverse histopathological changes were seen in the kidneys, liver, gills and intestines of Cyprinus carpio for T2(replacing fishmeal with 5% lentil) and T3 (replacing fishmeal with 10% lentil) in comparison with the control (T1). However, various levels of adverse histopathological changes were seen in the T4(replacing fish meal with 15% lentil) and T5 (replacing fishmeal with 20% lentil). In the kidneys, dilation of the Bowman’s spaces was evidently associated with a decrease in the mesangial cellularity of glomerular tuft. In the liver, congestion of the central vein was apparent together with centrilobular infiltration of inflammatory cells. In the gills, hyperplasia of primary and secondary lamellae was evident. In the intestine, vacuolar degeneration of the lining epithelial cells was apparent together with extravasation of RBCs associated with marked infiltration of inflammatory cells in the lamina propria. In conclusion, the partial replacement of the fishmeal in diets of C. carpio by crude lentil seeds was safe at the 5% and 10% levels as indicated by various levels of adverse histopathological effects on the kidneys, liver, gills, and intestine.